1978
DOI: 10.1007/bf00775966
|View full text |Cite
|
Sign up to set email alerts
|

Effect of biotin on phosphorylation, acetylation, methylation of rat liver histones

Abstract: Biotin deficient rat liver histones showed decreased phosphorylation and methylation, and increased acetylation rates as compared to normal rat liver histones: these alterations may be related to the observed lower stability of the interactions between histones and DNA. The modifications of the metabolic process might be the consequence of an alteration of the synthesis of the enzymes involved in histone phosphorylation, acetylation and methylation mechanisms and are presumably related to a biotin effect upon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1978
1978
2010
2010

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…In contrast, dimethylation of arginine residues enhances biotinylation of adjacent lysine residues (118). This is consistent with studies suggesting that histones in livers from biotin-deficient rats showed unusual patterns of phosphorylation, methylation, and acetylation compared with biotin-sufficient controls (99).…”
Section: Identification Of Biotinylation Sitessupporting
confidence: 90%
“…In contrast, dimethylation of arginine residues enhances biotinylation of adjacent lysine residues (118). This is consistent with studies suggesting that histones in livers from biotin-deficient rats showed unusual patterns of phosphorylation, methylation, and acetylation compared with biotin-sufficient controls (99).…”
Section: Identification Of Biotinylation Sitessupporting
confidence: 90%
“…As was demonstrated recently by Hymes and co-workers (55,56), human histones may be specifically biotinylated, in vivo, by the action of biotinidase functioning as a biotin transferase rather than as hydrolase. The packaging and regulatory properties of rat liver chromatin were shown be affected by a similar histone modification (59,60). Similarly, noncovalently associated biotinyl-AMP facilitates binding of the BirA aporepressor to the E. coli biotin operator (10,57,61).…”
Section: Discussionmentioning
confidence: 99%
“…134 In prostate cells, it has been demonstrated that hypoxia increases global DNA methylation and H3K9 histone acetylation. 136 Several dietary factors have been linked to increased histone acetylation (Table V), including biotin deficiency, 137 quercetin, 138 or caffeine. 136 Several dietary factors have been linked to increased histone acetylation (Table V), including biotin deficiency, 137 quercetin, 138 or caffeine.…”
Section: B Histone Modificationsmentioning
confidence: 99%